2012
DOI: 10.1093/nar/gks1131
|View full text |Cite
|
Sign up to set email alerts
|

Probing Rad51-DNA interactions by changing DNA twist

Abstract: In eukaryotes, Rad51 protein is responsible for the recombinational repair of double-strand DNA breaks. Rad51 monomers cooperatively assemble on exonuclease-processed broken ends forming helical nucleo-protein filaments that can pair with homologous regions of sister chromatids. Homologous pairing allows the broken ends to be reunited in a complex but error-free repair process. Rad51 protein has ATPase activity but its role is poorly understood, as homologous pairing is independent of adenosine triphosphate (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…We use Ca 2+ as the divalent cation as it inhibits ATP hydrolysis and thereby prevents protein dissociation, resulting in the formation of stable filaments (33,34). Assembly was monitored both by tracking the length increase of the DNA-tether determined from the beads’ z -position and by observing unwinding of the DNA determined by tracking the rotation angle about the DNA-tether axis [Figure 1b; note that in the FOMT configuration we determine the rotation angle by simply converting the tracked ( x , y )-position on the circular annulus of the bead’s free rotation and converting it to angle, see Supplementary Figure S1] (26,29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use Ca 2+ as the divalent cation as it inhibits ATP hydrolysis and thereby prevents protein dissociation, resulting in the formation of stable filaments (33,34). Assembly was monitored both by tracking the length increase of the DNA-tether determined from the beads’ z -position and by observing unwinding of the DNA determined by tracking the rotation angle about the DNA-tether axis [Figure 1b; note that in the FOMT configuration we determine the rotation angle by simply converting the tracked ( x , y )-position on the circular annulus of the bead’s free rotation and converting it to angle, see Supplementary Figure S1] (26,29).…”
Section: Resultsmentioning
confidence: 99%
“…During filament assembly, the magnet was rotated by ∼−310 turns (34) to relieve the accumulated torsional strain. Subsequently, the extension of the RAD51 filament (Figure 2b) and the torque stored in the filament (Figure 2c) were simultaneously measured as a function of turns.…”
Section: Resultsmentioning
confidence: 99%
“…Similar conformational transitions have also been observed for hRAD51 filaments on dsDNA. Experiments using magnetic tweezers (Ristic et al, 2005;Atwell et al, 2012) have shown that hRAD51 binds dsDNA in two distinct modes with different pitch and that, upon ATP hydrolysis, the NPFs can switch to a compact state before NPF disassembly. Changes in DNA twist can also trigger transitions between the two modes.…”
Section: Introductionmentioning
confidence: 99%
“…HR is a process that requires the presence of a homologous DNA region to serve as a template for accurate repair (2). RAD51, a recA homolog that forms helical filaments, binds to single-strand DNA, thus promoting recombinational repair (3,4). RAD51 knockout mice usually die at an early stage of embryogenesis, and cells lacking functional RAD51 often exhibit chromosome breaks and cell-cycle arrest (5,6).…”
mentioning
confidence: 99%